Child maltreatment and emergency department visits: a longitudinal birth cohort study from infancy to early adulthood. (January 2022) - Gnanamanickam, Emmanuel S.; Nguyen, Ha; Armfield, Jason M.; Doidge, James C.; Brown, Derek S.; Preen, David B.; Segal, Leonie
Abstract: Background: Child maltreatment (CM) is a serious global public health issue, with documented impacts on health. Objective: To examine the association between different levels of CM concern, and Emergency Department (ED) visits from infancy to early adulthood. Participants and setting: Individuals born in Adelaide, South Australia from January 1986 to June 2017 ( N = 443, 754). Methods: Using linked administrative data, we examined frequency and adjusted rate ratios for all-cause and cause specific ED visits among individuals with varying levels of CM concern. Results: Cumulative mean ED visits to age 14.5 years were higher for individuals with any CM concern, ranging from 10.2 to 14.8, compared with 6.4 in persons with no recorded CM concern. Adjusted rate ratios for ED visits varied from 1.26 (95% CI: 1.23–1.30) to 1.54 (1.48–1.60) in children (birth to 12 years), 1.98 (CI: 1.92–2.04) to 4.34 (CI: 4.09–4.60) in adolescence and 2.22 (CI: 2.14–3.48) to 3.48 (3.27–3.72) in young adults, increasing with severity of maltreatment concerns. ED visits coded as self-harm or poisoning, injuries, substance use or mental illness were particularly high, with incidence rate ratios mostly 3 to 15 times for mental health/substance related visits and 1.5 to 3.2 for other accidents or injury for individuals with any CM concern versus none. Conclusions: The high rate ratios for ED visits in children with CM concern, especially for self-harm, substance use and mental health during adolescence and adulthood highlights the enduring mental health needs of victims of child maltreatment, providing further impetus for prevention.